Factors Analysis on Biomethanation of Poultry Manure Wastewater - N., Zainol; Nina Farhana, Mohd Jamaludin (Research India Publications, 2014)
The need for low tech options for poultry manure treatment and application possibilities in agriculture is increasing by times in order to ensure low cost and profitable to be applied. In this study, factorial analysis was conducted for biomethanation of poultry manure wastewater (PMW). Two-level fractional factorial design (FFD) was used to construct experimental table, analyzed main factors and suggested best condition for the process. From the main effect analysis, agitation gave highest contribution at 24.09%, followed by type of substrate with 9.60% contribution. In term of interaction the agitation and process system gave highest contribution by 16.87%. The best suggested condition for the biomethanation of PMW was as follows: type of substrate (pre-treated PMW), process system (batch), substrate:inoculum (4:1), reaction time (3 days) and agitation (120 rpm). At this condition, predicted biogas yield was at 0.00974 L/g COD while the experimental biogas yield was at 0.00996 L/g COD.